(untitled) (Contemporary Mathematics, 2022)
In this paper, we extend the Traub theory for solving nonlinear equation. The extension is based on recurrent functions, the center Lipschitz condition and the notion of the restricted convergence domain. Numerical examples indicate that the new results can be utilized to solve nonlinear equations, but not earlier ones.